Evaluation of grain sorghum hybrids reveals potential for improving ruminal fermentation - Johnson, James Robert (Kansas State University, 2019)
In vitro incubations were used to compare fermentation characteristics of corn (uncharacterized hybrid) to 24 sorghum parental lines and hybrids (Clemson University; Richardson Seeds Inc., Lubbock, TX; Scott Seed Company, Hereford, TX). Two in vitro experiments were conducted as randomized complete block designs using ruminal contents from two ruminally-fistulated steers (blocks). Grains were ground to similar consistency (1-mm screen) and used as substrates (2 g; DM basis) in laboratory fermenters containing strained ruminal contents and bicarbonate buffer. Fermenters were equipped with pressure-monitoring devices (ANKOM Technology, Macedon, NY) to measure gas production. Gas production, organic acid production, terminal pH of cultures, and dry matter disappearance were used as indicators of microbial digestion. Cultures were incubated for 24 (experiment 1) to 30 hours (experiment 2), with gas production recorded at 15-minute intervals. Experiment 1 compared corn to 23 sorghum cultivars, and experiment 2 compared corn to six sorghum cultivars, five of which were represented in experiment 1, plus one waxy hybrid. Data were analyzed using the MIXED procedure of SAS version 9.1 (SAS Inst. Inc., Cary, NC), with treatment as the fixed effect and block as the random effect. For gas production data, time and the interaction between time and cultivar also were used as fixed effects. For both in vitro experiments, there was an interaction between cultivar and time (P < 0.0001) for gas production, revealing large differences among cultivars with respect to their relative susceptibilities to microbial digestion. Similarly, DM disappearance; production of acetate, propionate, and butyrate; and acetate:propionate varied substantially among cultivars (P < 0.01) and in many cases exceeded measurements obtained with the corn control. A backgrounding study also was conducted to evaluate performance in crossbred steers (n=120, initial BW 273.08 kg ± 2.94) fed diets containing dry-rolled corn, ground 341x120 sorghum hybrid, or ground waxy sorghum diet. Daily feed intakes were monitored for individual animals using the RIC Feeding System (Hokofarm, Netherlands). Feeding ground sorghum-based diets to backgrounding steers increased DMI by 0.51 kg/d ± 0.18 when compared to the dry rolled corn diet. Gain efficiency (G:F; P = 0.36) was not influenced by grain source, but ADG (P < 0.005) was greater for cattle fed waxy sorghum compared with other treatments. Compared to corn, feeding waxy sorghum increased final BW (P < 0.003), but BW of cattle fed the 341x120 cultivar was not different from other treatments (P = 0.12). Sorghum cultivars used in these experiments revealed substantial heterogeneity with respect to their susceptibilities to digestion by ruminal microorganisms. Additionally, the backgrounding experiment revealed potential for sorghum cultivars to compete with corn as energy sources in cattle production.
Keywords: In vitro; Sorghum grain; Feedlot; Microbial fermentation